Grammar Builder 1 : a grammar guidebook for students - Amin, A.; Eravelly, R.; Ibrahim, F. J. (Cambridge : New York : Cambridge University Press, 2007)
Helps learners of British English master key concepts in grammar easily and quickly.
Keywords: English language -- Grammar; English language -- Textbooks for foreign speakers; English language